Metastatic colonic and gastric polyps from breast cancer resembling hyperplastic polyps - Yoshiya Horimoto; Tetsuro Hirashima; Atsushi Arakawa; Hiroyoshi Miura; Mitsue Saito (Surgical Case Reports)
Abstract Breast cancer metastasis to the gastrointestinal tract is relatively rare and is generally found when patients complain of symptoms such as gastrointestinal obstruction. Herein, we report a case with metastatic colonic and gastric lesions from breast cancer, with the formation of mucosal polyps which resembled typical hyperplastic polyps. A 47-year-old woman underwent curable surgery for breast cancer and received standard systemic treatments. Her primary tumor was composed of a mix of invasive lobular and ductal carcinomas. During adjuvant endocrine therapy, she developed multiple colonic metastases, identified by colonoscopy performed as part of a general health check-up. She had no symptoms. Small elevated sessile polyps in the transverse colon and rectum showed histological features of signet-ring cell type adenocarcinoma, similar to the invasive lobular component of the primary breast cancer. During treatments for recurrent disease, she also developed multiple gastric metastases, with the same endoscopic and pathological features as the colonic lesions. Her treatment regimen was switched to oral chemotherapy, and she has since maintained stable disease for nearly 3 years. Multiple bone metastases eventually developed, and she was again switched to another systemic treatment but, to date, has remained free of symptoms. We emphasize that the endoscopic findings of the metastatic lesions in the colon and stomach in this case highly resembled hyperplastic polyps. Since biopsy is not always performed for hyperplastic polyps in the gastrointestinal tract, we believe that this case report may encourage endoscopists to offer biopsies to the patient who has a history of breast cancer.